2020
DOI: 10.1051/matecconf/202033001037
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-electrical analogy and inertia for thermal performance of building envelops

Abstract: For transient thermal performance of building envelops adequate parameters are needed to capture the time lag and decrement factor. It is surprising that, in the formal electrical analogy, "inertia" is not represented by same components in fluid mechanics and heat transfer. In Windkessel model for fluid flow in elastic tubes, the fluid inertia is represented by an electrical inductance while in thermal-electric analogy, thermal inertia is given by a capacitance. Some authors argued that the terminology of ''th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In [22], it is shown that such an analogy can be used in modeling transient heat flow. Such analogies are used in the modeling, analysis, and control of thermal systems [23][24][25][26][27]. Modeling of such thermal resistances is also important for the thermal dynamics of the electric current-activated/assisted sintering systems [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In [22], it is shown that such an analogy can be used in modeling transient heat flow. Such analogies are used in the modeling, analysis, and control of thermal systems [23][24][25][26][27]. Modeling of such thermal resistances is also important for the thermal dynamics of the electric current-activated/assisted sintering systems [28][29][30].…”
Section: Introductionmentioning
confidence: 99%